IMMU-10. TUMOR ASSOCIATED MYELOID CELLS DRIVE THE IMMUNOBIOLOGY OF HIGH RISK PEDIATRIC EPENDYMOMA. (3rd June 2022) - Griesinger, Andrea; Riemondy, Kent; Eswaran, Nithyashri; Donson, Andrew; Willard, Nicholas; Paine, Simon; Bowes, Georgia; Rheaume, John; Chapman, Rebecca; Ramage, Judith; Jackson, Andrew; Grundy, Richard; et al.
Abstract: Molecular profiling of pediatric ependymoma (EPN) has previously identified discrete neoplastic subpopulations, of which Mesenchymal EPN Cells (MEC) characterize Posterior Fossa A tumors (PFA). MECs are associated with tumor immunosuppression. Here we further characterize the EPN immune environment using single-cell sequencing, spatial phenotyping and cytokine analyses to better define infiltrating myeloid subpopulations. We hypothesize that neoplastic and myeloid cells interact to propagate an immune suppressive environment conferring resistance to traditional therapies. We delineated myeloid cell subpopulations from single-cell RNA-seq of 26 pediatric EPNs and validated them through deconvolution of bulk gene expression profiling (n=299). To define subpopulation spatial distribution, we interrogated a range of tumor and myeloid markers using multiplex immunofluorescence (mIF). Finally, using single-cell cytokine analyses, we gained further insight into myeloid subpopulation function. Eight distinct myeloid subpopulations were identified, relating to macrophages, microglia and monocytes. A subpopulation of cells with wound healing ontologies and characterized by TREM1 expression, demonstrated features of myeloid derived suppressor cells, including IL6/STAT3 pathway activation. We called these hypoxia-M. Like MEC neoplastic cells, hypoxia-M was associated specifically with PFA1 subgroup EPN in both single-cell and bulk tumor gene expression profiling (p<0.001). Additionally, the presence of MEC and hypoxia-M correlated strongly in gene expression (r2=0.92, p<0.001) and IHC analyses, where they co-located to borders between necrosis, blood vessels and viable tumor. Analysis using mIF (n=54) confirmed MEC/hypoxia-M co-location and highlighted that all types of immune cell corralled in significant numbers around areas of vasculature and necrosis. Single cell cytokine analyses demonstrated that hypoxia-M secrete IL-8 which, we hypothesize, amplify the pro-tumor phenotype in PFA1 tumor microenvironment. EPN is characterized by discrete myeloid cell subpopulations which contribute to the tumor microenvironment. Treatment strategies must focus on modifying this pro-tumor, immunosuppressive microenvironment to deliver more effective treatment for childhood ependymoma.